Factor V Leiden G1691A and prothrombin G20210A mutations among Palestinian patients with sickle cell disease - Samarah, Fekri (BMC Hematol, 2018)
BACKGROUND: Vascular thrombosis is an important pathophysiological aspect of sickle cell disease (SCD). This study aimed to investigate the prevalence and clinical impact of factor V Leiden G1691A (FVL) and prothrombin G20210A mutations among Palestinian sickle cell disease (SCD) patients. METHODS: A total of 117 SCD patients, including 59 patients with sickle cell anemia (SS), 33 patients with sickle β-thalassemia and 25 individuals with sickle cell trait (AS) were studied. The control group consisted of 118 healthy individuals. FVL and prothrombin G20210A mutations were determined by RFLP PCR. RESULTS: Analysis of the clinical history of SCD patients revealed that seven patients have had vascular complications such as ischemic stroke or deep vein thrombosis. In SCD patients, the inheritance of the FVL mutation showed a significantly higher incidence of pain in joints, chest and abdomen as well as regular dependence on blood transfusion compared to SCD with the wild type. Age- and sex-adjusted logistic regression analysis revealed a significant association between FVL and sickle cell anemia with an odds ratio (OR) of 5.6 (95% confidence intervals [CI] of 1.91–39.4, P = 0.039) in SS patients. However, increased prevalence of the FVL in AS subjects and sickle β-thalassemia patients was not statistically significant compared to controls (OR 3.97, 95% CI 0.51–28.6, P = 0.17 and OR 3.59, 95% CI 0.35–41.6, P = 0.26, respectively). The distribution of prothrombin G20210A mutation among SCD patients compared to controls was not significantly different, thus our findings do not support an association of this mutation with SCD. CONCLUSIONS: FVL was more prevalent among SS patients compared to controls and it was associated with higher incidence of disease complications among SCD patients.